The Birth and Growth of Porsild Pingo, Tuktoyaktuk Peninsula, District of Mackenzie - Mackay, J. Ross (ARCTIC, 1988)
The birth and growth of Porsild Pingo (ice-cored hill) can be taken as fairly representative of the birth and growth of the more than 2000 closed-system pingos of the western arctic coast of Canada and adjacent Alaska. Porsild Pingo, named after a distinguished arctic botanist, has grown in the bottom of a large lake that drained catastrophically about 1900. Porsild Pingo has grown up at the site of a former shallow residual pond. The "birth" probably took place between 1920 and 1930. The high pore water pressure that caused updoming of the bottom of the residual pond to give birth to Porsild Pingo came from pore water expulsion by downward and upward permafrost growth in saturated sands in a closed system. In the freeze-back period of October-November 1934, permafrost ruptured and the intrusion of water into the unfrozen part of the active layer grew a 3.7 m high frost mound photographed by Porsild in May 1935. Porsild Pingo has grown up at, or very close to, the site of the former frost mound. The growth of Porsild Pingo appears to have been fairly steady from 1935 to 1976, after which there has been a decline to 1987. The growth rate has been nearly linear with height, from zero at the periphery to a maximum at the top. The present addition of water to the pingo is about 630 cu m/y. Providing there is no major climatic change. Porsild Pingo may continue to grow for a few centuries.Key words: frost mound, intrusive ice, permafrost, pingo, Porsild Mots clés: monticule de gel, glace d’intrusion, pergélisol, pingo, Porsild